Franciszek Maciejowski on the Law of the XII Tables - Zabłocka, Maria; Zabłocki, Jan (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
In the first textbook on Roman law published in Polish language, The Principles of Roman Common Law [i.e. Civil Law] based on the Institutions of Justinian, containing also a brief excursus on the historical development of Roman legislation, Franciszek Maciejowski quoted several provisions of the Law of the Twelve Tables, without however providing their translation. Not all the provisions quoted by him came from Gothofredus’ Palingenesis, as declared by the author, but some of them originated from an earlier work constituting an attempt to systematise the work of Decemvirs, i.e. Oldendorp’s work, which passed unnoticed by Maciejowski.